Global trends in ambient particulate matter-attributable ischemic heart disease among the elderly (1990–2021) - Zeng, Yangxi; Liu, Lihui; Huang, Gang; Liu, Can; Lan, Xi; Mou, Yuhan; Wang, Xinyu; Liao, Bin; Wan, Juyi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAirborne particulate matter (PM), particularly PM₂.₅, poses a growing threat to cardiovascular health, especially among older adults. With intensified urbanization and industrial activities, PM₂.₅ has become a major factor contributing to ischemic heart disease (IHD), a leading cause of global mortality. These fine particles can penetrate pulmonary defenses, enter circulation, and trigger inflammatory and oxidative pathways that accelerate vascular damage. The elderly, whose physiological resilience declines with age, are particularly susceptible. While PM exposure's link to IHD is established, patterns by sex and age in older populations remain underexplored. This study assesses global, regional, and national shifts in PM-related IHD burden between 1990 and 2021, identifies disparities across demographics, and examines the influence of socioeconomic development. It also forecasts trends to 2040, providing insights to guide public health interventions for aging societies.MethodsUsing the Global Burden of Disease study (GBD 2021), we analyzed mortality and disability-adjusted life years (DALYs) from 1990 to 2021 across global, regional, and national levels. We calculated age-standardized rates (ASRs) and estimated annual percentage changes (EAPCs). Future trends were projected using a Bayesian age–period–cohort (BAPC) model. Modelling was performed in R, disaggregated by sex and age, linked with PM exposure and socioeconomic development.ResultsOverall IHD due to PM declined globally from 1990 to 2021. The largest reductions occurred in high-SDI regions. Burden increased in low- and middle-income areas in Asia and Africa. Globally, IHD burden from PM was negatively correlated with sociodemographic index (SDI). Men had higher burdens than women, with differences increasing by age. Although BAPC projections indicate a continued decline, a potential rise in pollution around 2035 may slow the rate of decrease or temporarily flatten the downward trajectory.ConclusionAlthough global declines have been observed, the burden of ischemic heart disease (IHD) attributable to ambient particulate matter pollution remains persistently high in Southeast Asia and Africa. Forecasts suggest that elderly individuals, particularly men, will continue to experience disproportionate health impacts in the coming decades. Targeted public health initiatives focused on reducing particulate matter exposure, especially among vulnerable aging populations, are essential to mitigate future cardiovascular risks and promote healthy aging worldwide.